"It's Like a Death Sentence but It Really Isn't" What Patients and Families Want to Know About Hospice Care When Making End-of-Life Decisions. (September 2020) - Tate, Channing E.; Venechuk, Grace; Brereton, Elinor J.; Ingle, Pilar; Allen, Larry A.; Morris, Megan A.; Matlock, Daniel D.
Background: Hospice is underutilized, due to both lack of initiation from patients and late referral from clinicians. Prior research has suggested the reasons for underuse are multifactorial, including clinician and patient lack of understanding, misperceptions about the nature of hospice care, and poor communication during end-of-life discussions about hospice care. Little is known about the decisional needs of patients and families engaging in hospice decision-making. Objectives: To understand the decisional needs of patients and families making decisions about hospice care. Methods: We conducted focus groups with family caregivers and hospice providers and one-on-one interviews with patients considering or enrolled in hospice care. We identified participants through purposeful and snowball sampling methods. All interviews were transcribed verbatim and analyzed using a grounded theory approach. Results: Four patients, 32 family caregivers, and 27 hospice providers participated in the study. Four main themes around decisional needs emerged from the interviews and focus groups: (1) What is hospice care?; (2) Why might hospice care be helpful?; (3) Where is hospice care provided?; and (4) How is hospice care paid for? Discussion: Hospice may not be the right treatment choice for all with terminal illness. Our study highlights where patients' and families' understanding could be enhanced to assure that they have the opportunity to benefit from hospice, if they so desire.